Quality Assurance Cadre of Assisted Teachers at Miftahul Ulum Lumajang Islamic Boarding School - Ahmad Zarkasyi (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2021)
Abstract Pesantren Miftahul Ulum Lumajang is an institution with quality assurance standards for the regeneration of ulama 'and dai with systemized characteristics. Quality assurance is systematic planning in the application of quality management to ensure that a product or service meets quality requirements from start to finish. This research is qualitative research with a field research approach. In this study, data analysis was carried out since data collection was reviewed as a whole. Based on the research findings, the quality assurance system for the regeneration of auxiliary teachers at the Miftahul Ulum Lumajang Islamic Boarding School is carried out on the dimensions of the guarantee system on the cadre side, the guarantee system on the object of regeneration, namely students, and finally the guarantee system in the Islamic boarding school curriculum. Keywords: Quality Assurance; Cadre; Assisted Teachers; Pesantren Abstrak Pesantren Miftahul Ulum Lumajang adalah lembaga yang memiliki standar penjaminan mutu untuk kaderisasi ulama 'dan dai dengan karakteristik yang tersistem. Penjaminan Mutu adalah perencanaan sistematis dalam penerapan manajemen mutu untuk memastikan bahwa suatu produk atau jasa memenuhi persyaratan mutu dari awal sampai akhir. Penelitian ini merupakan penelitian kualitatif dengan pendekatan penelitian lapangan. Dalam studi ini, analisis data dilakukan sejak pengumpulan data diperiksa ulang secara keseluruhan. Berdasarkan temuan penelitian. Berdasarkan temuan penelitian, sistem penjaminan mutu kaderisasi guru bantu di Pondok Pesantren Miftahul Ulum Lumajang dilakukan pada dimensi sistem penjaminan pada pihak pengkader, sistem penjaminan pada objek kaderisasi yaitu santri, dan terakhir adalah sistem penjaminan pada kurikulum pondok pesantren. Kata kunci: Penjaminan Mutu; Kaderisasi; Guru Bantu; Pesantren